Chinese hypertriglycerideamic subjects of different ages responded differently to consuming oil with medium- and long-chain fatty acids - Xue, C.(Chinese PLA General Hospital, Beijing (China)); Liu, Y; Wang, J; Zheng, Z; Zhang, Y; Zhang, R; Yu, X; Jin, H; Nosaka, N; Arai, C; Kasai, M; Aoyama, T; et al. (Bioscience, biotechnology, and biochemistry, 2009)
Two groups of Chinese hypertriacylglycerolemic subjects were recruited and randomized to medium- and long-chain triacylglycerols (MLCT) oil or long-chain triacylglycerols (LCT) oil. Two subgroups were divided by age at less or more 60 years in both groups. Both oils were consumed at 25-30 g daily for 8 weeks. Anthropometry, blood biochemicals, and computed tomography (CT) scanning were done at the initial and final times. In subjects of age less than 60 years on MLCT, the body weight, body mass index (BMI), waist circumference (WC), hip circumference (HC), waist-hip ratio (WHR), body fat, total fat area, and subcutaneous fat area were significantly lower than those of the initial values, and the change values in these indicators and visceral fat area lowered significantly as compared with those on LCT. The levels of apoB, apoA2, apoC2, and apoC3 decreased significantly, and the change in values in the levels of triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), apoA1, apoB, apoA2, apoC2, apoC3 were significantly lower on MLCT of age under 60 years as compared with those on LCT.